CHAOTIC BEHAVIOR OF MODIFIED HAMILTONIAN â PBD EQUATION ON DNA SYSTEM - EKA PUTRA SUTANTYO (NIM : 20216036), TRENGGINAS
DNA (Deoxiribose Nucleat Acid) is a material that carries the genetic information, that plays a role in the process of growth (autosomes) and reproduction (genosomes) in living things. DNA research has involved a variety of disciplines across fields, which work complementary and supportive with the tools of theory, model, and experiment. Physics provides a theoretical basis that can be used for experimentation, as well as developing new physical models. This physical model can explain the non-linear dynamics of DNA. In this study, DNA system was modeled by modifying the Peyrard-Bishop-Dauxois (PBD) DNA model. The influence of the surrounding environment, namely thermal bath is added to the Hamiltonian PBD, in the form of time-dependent thermal friction and stochastic white noise. Both are represented through the Nose-Hoover-Langevin (NHL) thermostat. Equation motion formulations were obtained using analytical methods, to be solved using numerical methods. The results from numerical calculations are presented in phase space images to show chaotic behavior. The results are obtained that there is an increase in chaotic patterns along with the increase in temperature. In addition, results also obtained that there is a relationship between widening of base pair distance at any time with temperature, especially in the denaturation process.